(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper addresses one way of locating entities in static spatial situations: the spatial deixis. Our main purpose is to describe the structure and use of the demonstrative system in small-scale space in the language spoken by Gypsies in Chile: the rromané jorajané. Data collection was performed with “The 1999 Demonstrative Questionnaire: ‘THIS’ and ‘THAT’ in comparative perspective” (Wilkins, 1999). The analysis results highlight that spatial demonstratives in rromané jorajané are a highly symmetrical group combining a deictic semantic component (the proximal-distal distinction) with grammatical contents (gender and number). It is a binary demonstrative system in terms of the category of distance from the deictic center. Additionally, it is concluded that choice of the suitable demonstrative proceeds according to the following pattern: the proximal demonstrative has its focal area in the speaker’s zone of proximity, while the distal demonstrative includes both the addressee’s zone of proximity and the speaker’s distal zone within its application field.